Tuning the Bandgap Character of Quantum‐Confined Si–Sn Alloyed Nanocrystals. (2nd April 2020) - Bürkle, Marius; Lozac'h, Mickaël; McDonald, Calum; Macias‐Montero, Manuel; Alessi, Bruno; Mariotti, Davide; Švrček, Vladimir
Abstract: Nanocrystals in the regime between molecules and bulk give rise to unique electronic properties. Here, a thorough study focusing on quantum‐confined nanocrystals (NCs) is provided. At the level of density functional theory an approximate (quasi) band structure which addresses both the molecular and bulk aspects of finite‐sized NCs is calculated. In particular, how band‐like features emerge with increasing particle diameter is shown. The quasiband structure is used to discuss technological‐relevant direct bandgap NCs. It is found that ultrasmall Sn NCs have a direct bandgap in their at‐nanoscale‐stable α‐phase and for high enough Sn concentration (≈41%) alloyed Si–Sn NCs transition from indirect to direct bandgap semiconductors. The calculations strongly support recent experiments suggesting a direct bandgap for these systems. For a quantitative comparison many‐body GW + Bethe–Salpeter equation (BSE) calculations are performed. The predicted optical gaps are close to the experimental data and the calculated absorbance spectra compare well with the corresponding measurements. Abstract : Direct bandgap group IV semiconductors increase absorption and are more favorable for many applications. Here, the transition from indirect to direct bandgap in ultrasmall binary silicon/tin nanocrystals is elucidated. State‐of‐the‐art first‐principle calculations predict the transition threshold depending on the Sn concentration and the corresponding optical properties. The threshold for nanocrystals differs significantly from what is expected for bulk.